2015
DOI: 10.1021/acscatal.5b01968
|View full text |Cite
|
Sign up to set email alerts
|

“Stable-on-the-Table” Enzymes: Engineering the Enzyme–Graphene Oxide Interface for Unprecedented Kinetic Stability of the Biocatalyst

Abstract: A rational strategy is presented here to enhance enzyme stability by gaining control over the noncovalent interactions at the enzyme–graphene interface (EGI). The charge (n) on a model enzyme, glucose oxidase (GOx), was systematically varied from −67 to +78 via chemical modification of its COOH groups with polyamines, and chemically modified GOx­(n) has been adsorbed onto graphene oxide (GO). Control of the net charge on GOx­(n) provided an excellent handle to engineer the EGI to enhance the stability of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…One of the important aims of enzyme immobilization is to achieve high enzyme stability at harsh conditions such as high temperature and organic solvents which often existe in industrial biocatalytic processes. Although immobilization may compromise the activity of enzyme, the greatly enhanced stability would enable the long-term and repeated use of enzyme and therefore a significantly reduced cost of enzyme (Liu et al 2015 ; Liang et al 2016a ; Ji et al 2016 ; Novak et al 2015 ). Metal-organic frameworks (MOFs) have emerged as a new type of nanomaterials suitable for immobilization of enzyme (Feng et al 2015 ; Lykourinou et al 2011 ; Chen et al 2012 ; Wen et al 2016 ) and other biomolecules (Zhang et al 2016 ; Li et al 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important aims of enzyme immobilization is to achieve high enzyme stability at harsh conditions such as high temperature and organic solvents which often existe in industrial biocatalytic processes. Although immobilization may compromise the activity of enzyme, the greatly enhanced stability would enable the long-term and repeated use of enzyme and therefore a significantly reduced cost of enzyme (Liu et al 2015 ; Liang et al 2016a ; Ji et al 2016 ; Novak et al 2015 ). Metal-organic frameworks (MOFs) have emerged as a new type of nanomaterials suitable for immobilization of enzyme (Feng et al 2015 ; Lykourinou et al 2011 ; Chen et al 2012 ; Wen et al 2016 ) and other biomolecules (Zhang et al 2016 ; Li et al 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of enzymatic biosensors, the key to a good device is the immobilization of the enzyme onto the electrode surface. It has been reported that with the usage of graphene the denaturation of the enzyme is avoided, and the thermodynamic stability is improved generating in this way an excellent biocatalysis . For this reason graphene has been used as immobilization platform of various enzymes (ex.…”
Section: Applicationsmentioning
confidence: 99%
“…Oxidase activity of GOx was measured using D-glucose as a substrate by a known colorimetric method. 18 2.2h Self-degrading gels: BSA/ARG (75 mg/mL/ 100 mM) was prepared, as mentioned above, with the exception that trypsin (0.33 and 1 mg/mL) was dissolved in the BSA solution before gelation. Degradation of the gel by proteases with respect to temperature was measured by incubating the gel matrix in the buffer at 37 • C, in a water bath.…”
Section: 2g Enzyme Activitymentioning
confidence: 99%